(Un)Disciplined futures: Women of color feminism as a disruptive to white affect studies. Issue 3 (3rd July 2017) - Garcia-Rojas, Claudia
ABSTRACT: The aim of this article is to demonstrate how women of color feminism predates and disrupts dominant dialogues in the field of White affect studies. I introduce the concept of White affect studies as an arena of inquiry that draws from Western-European theories and literatures and architects a sociopolitical structure of affect that positions White affects as universal. Scholars contributing to the field of White affect studies posit theories of affect, embodiment, subjectivity, phenomenology, violence, war, and more, while disregarding the theoretical contributions made by women of color feminism in thinking through these notions and social issues. This is done by engaging in a citational practice that results in an epistemic erasure of women of color feminist thought. The voices of women of color feminists are thus disqualified, and their theoretical contributions are not acknowledged as significant or relevant in conceptualizing affect, affective economies, and the social. By turning to the writings of women of color feminists, I demonstrate how their theories on embodiment, subjectivity, and social structures predate the institutionalization of White affect studies. Feminists of color from the past and present have and continue to theorize through a language of self their experiences as subjects embedded within matrices of violence, power, and pleasure. Lorde, Martinez, and Chinchilla write about the ways in which lesbian and queer women of color institute different affects that counter dominant structures of emotion, systems of power, and heterosexual modes of being. In developing conceptual methodologies, Lorde, Martinez, and Chinchilla are able to weave into the dominant discursive logic a language of self that both introduces new queer subjectivities, while reinterpreting existing forms of thought, thereby contesting mainstream economies of White affects and White affect studies. It is through a language of self that Lorde, Martinez, and Chinchilla develop an ethic of survival that countermobilizes against White hegemonic apparatuses.